2022
DOI: 10.1590/1980-549720220037
|View full text |Cite
|
Sign up to set email alerts
|

Trend of traffic accident mortality rate among motorcyclists in the state of São Paulo, Brazil, from 2015 to 2020

Abstract: Objective: To assess the trend in motorcyclist mortality rate from traffic accidents in the state of São Paulo, Brazil, from 2015 to 2020. Methods: This is an ecological time series study with secondary data from the Traffic Accident Management Information System of the State of São Paulo (INFOSIGA), referring to motorcyclists’ deaths due to road traffic injuries in the state of São Paulo, Brazil, from 2015 to 2020. The Annual Percent Change was calculated according to the Prais-Winsten regression model, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Considering public policies, in the city of São Paulo, São Paulo, Brazil, in the period from 2010 to 2016, it was found that, after the reduction of maximum speed on public roads, the decline in mortality from traffic accidents was accentuated. For men, the mortality rate was from 18.46 to 10.99 per 100,000 inhabitants and, for women, from 3.66 to 2.80 per 100,000 inhabitants, differences that are significantly relevant 25,26 .…”
Section: Sex and Mortality From Road Traffic Accidentsmentioning
confidence: 93%
“…Considering public policies, in the city of São Paulo, São Paulo, Brazil, in the period from 2010 to 2016, it was found that, after the reduction of maximum speed on public roads, the decline in mortality from traffic accidents was accentuated. For men, the mortality rate was from 18.46 to 10.99 per 100,000 inhabitants and, for women, from 3.66 to 2.80 per 100,000 inhabitants, differences that are significantly relevant 25,26 .…”
Section: Sex and Mortality From Road Traffic Accidentsmentioning
confidence: 93%